Design and Creative Methods as a Practice of Liminality in Community-Academic Research Projects. (4th July 2018) - Lam, Busayawan; Phillips, Martin; Kelemen, Mihaela; Zamenopoulos, Theodore; Moffat, Susan; de Sousa, Sophia
Abstract: This paper aims to explore the types of spaces and experiences that are created by design and creative practices. More specifically, it focuses on how design and creative practices can engender transformations in the mindset, knowledge, emotions and social relations of people who participate in such practices. To do this, the paper investigates the concepts of liminality and liminal spaces, and the relationships between design/creative methods and liminal spaces using insights from four case studies. The results reveal that design and creative practices may create liminal spaces in many ways, such as neutralizing the working environments, encouraging people to experiment with new ideas and helping them express themselves more freely.